Pemanfaatan Media Sosial Sebagai Wadah Promosi Produk Rumahan Bagi Perempuan Nelayan di Desa Ranto Panyang Kecamatan Meureubo - Desi Maulida; Safrida Safrida; Nodi Marefanda (Universitas Teuku Umar, 2020)
The presence of social media is currently contributing greatly in product marketing. It is important to educate the use of social media to businesses, including fishermen wives in marketing processed fish products in order to help improve the economics of fishing families. The method used in this socialization is to provide an understanding of the benefits and ways of using social media such as Facebook, Instagram, and YouTube in product marketing. The results of the socialization show that, the majority of fishermen's wives are not very aware of the benefits offered by social media in helping them market their products. Product marketing is still done traditionally, that is, offering it directly to people with the closest distance. This socialization is expected to be able to foster awareness that there will be many conveniences obtained when using social media as an effective promotional medium and be able to reach far more consumers which will have an impact on increasing the number of product sales, so that it will indirectly be able to improve the economic of fishermen families in the village Ranto Panjang, Meurebo District.